2008
DOI: 10.1186/1550-2783-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbohydrate-protein supplement timing on acute exercise-induced muscle damage

Abstract: PurposeTo determine if timing of a supplement would have an effect on muscle damage, function and soreness.MethodsTwenty-seven untrained men (21 ± 3 yrs) were given a supplement before or after exercise. Subjects were randomly assigned to a pre exercise (n = 9), received carbohydrate/protein drink before exercise and placebo after, a post exercise (n = 9), received placebo before exercise and carbohydrate/protein drink after, or a control group (n = 9), received placebo before and after exercise. Subjects perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 29 publications
6
62
0
3
Order By: Relevance
“…Additionally, in accordance to our study, White et al 2 , Breen et al 18 , Betts et al 19 , and Green et al 20 showed that the co-ingestion of CHO and PRO does not improve the recovery of isometric force.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Additionally, in accordance to our study, White et al 2 , Breen et al 18 , Betts et al 19 , and Green et al 20 showed that the co-ingestion of CHO and PRO does not improve the recovery of isometric force.…”
Section: Discussionsupporting
confidence: 75%
“…That is because most studies showing significant effects have maximum CK levels between 250 and 600 U/L 10,11,14,35 , while those showing no significant effects have typically reported peak CK levels in the 1000-1400 U/L region 2,20 . Considering that the subjects in the present study already had high plasma CK before the LRT, it is reasonable to suppose that our results could have been influenced by this fact, which makes comparison particularly difficult since in other studies subjects usually had normal CK before performing physical tests.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research relating to EIMD suffers from a limitation, which is often acknowledged, in that there is a lack of control concerning habitual diet (Cockburn et al, 2008, Howatson et al, 2012, White et al, 2008. This is problematic on two counts; with underlying discrepancies in macronutrient intake affecting bioavailability of a given substrate and a likely variance in the energy balance within or between experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence is equivocal, with research suggesting efficacy (Cockburn et al, 2008, Etheridge et al, 2008, Hoffman et al, 2010) and a lack of benefits (Green et al, 2008, White et al, 2008, Wojcik et al, 2001) for protein or coingested-protein supplementation to attenuate indices of EIMD. Fractional synthesis rates and fractional net balance are still elevated at 48 h following resistance exercise (Phillips et al, 1997).…”
mentioning
confidence: 99%
“…29,30 Elevated levels of these enzymatic markers are associated with decreased performance. 30 Due to the applied nature of recovery studies, the majority of the literature examining muscle damage has included multiple indicators of muscle damage: bloodborne creatine kinase (CK), subjective measures of muscle soreness (using a visual scale). 31 However, CK has been criticised as an effective indicator of muscle damage because of poor correlations with direct measures of muscle damage.…”
Section: 1321252728mentioning
confidence: 99%